Managerial Competence as the Key Driver of INA-CBGs Claim Optimization under National Health Insurance Program (Jaminan Kesehatan Nasional) Policy - Aristya Indah Widiyanti; Ediansyah Ediansyah; Yanuar Ramadhan (Digital Innovation : International Journal of Management, 2026)
This study investigates the optimization of claims under the Indonesian Case-Based Groups (INA-CBGs) payment mechanism within the National Health Insurance Program (Jaminan Kesehatan Nasional) at Hospital X in Serang. The research aims to analyze the influence of managerial competence, digital adoption, and organizational behavior on claim effectiveness, with policy implementation serving as a moderating variable. Employing a quantitative explanatory approach, data were collected from 144 respondents comprising management staff, casemix teams, and medical record officers through questionnaires and structured interviews. Structural Equation Modeling–Partial Least Square (SEM-PLS) was applied to examine the relationships among variables. Findings reveal that managerial competence, digital adoption, and organizational behavior significantly and positively affect the optimization of INA-CBGs claims. Furthermore, the implementation of the National Health Insurance Program policy strengthens these relationships, enhancing claim efficiency and equity. The results align with the Resource-Based View theory, highlighting the strategic role of internal resources in achieving organizational performance. Managerial implications include capacity building for managers, integration of hospital information systems (SIMRS) with e-Claim platforms, and fostering collaborative organizational culture. Overall, the study underscores the importance of managerial, technological, and behavioral factors, moderated by policy implementation, in improving hospital claim optimization under the INA-CBGs system.